DISORDERS OF THE LIPIDS METABOLISM AND CHANGES OF MAO ACTIVITIES AT THE DYLATATION CARDIOMYOPATHY - Kosimov I.S. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
According to WHO data, among cardiovascular diseases, cardiomyopathies account for a significant cause of mortality every year, taking many lives. In primary cardiomyopathy, dilation of the heart ventricles and chronic heart failure are observed. In many cases, its development may be due to the combined effect of coronary heart disease (CHD) and risk factors, among which is an increase in the level of low-density lipoproteins (LDL) in the blood serum. The term "cardiomyopathy" was first proposed by Bridgen in 1957 to describe myocardial disease of unknown origin, characterized by ECG changes, progressive circulatory failure, and potentially fatal outcomes. Godwin also supported this explanation of cardiomyopathy and conducted fundamental research from 1961 to 1982, classifying cardiomyopathy into three groups: dilated, hypertrophic, and restrictive. However, the definition of "cardiomyopathy" by the WHO is somewhat controversial, as the term is used in a very broad sense. For example, so-called "specific cardiomyopathies" include myocardial dysfunction due to CHD ("ischemic cardiomyopathy"), and due to heart valve disease ("valvular cardiomyopathy"), among others. Dilated cardiomyopathy is characterized by the dilation of the left or both ventricles and impaired myocardial contractility. Depending on the cause, it may be familial/hereditary, viral or immune, alcoholic (toxic), idiopathic (of unknown origin), or related to cardiovascular diseases where the degree of myocardial dysfunction is not clearly determined. In modern medicine, diagnostic criteria for cardiomyopathies are still insufficient. The interrelationship between monoamine oxidase (MAO) activity and lipid metabolism alterations sparked our interest.